OPTIMASI ALAT BAKAR SAMPAH DOMESTIK MILIK DESA PANDES, KECAMATAN WEDI, KABUPATEN KLATEN - Yohanes Agus Jayatun; Wahyu Endah Christiani; Herna Herna (Retii, 2022)
Pandes Village is a village in Klaten Regency which has a waste problem. One of the biggest problems of waste is non-biodegradable waste such as baby diapers, adult diapers and sanitary napkins. The productivity of non-reusable waste in Pandes Village in the form of waste used for children's diapers, adult diapers and community sanitary napkins is 3.69 tons/week. Partner's Problems and Solutions is that the capacity for processing waste burning equipment is still not sufficient to meet the needs of the community, so it is necessary to optimize the ability to use these tools.The purpose of this program for the TPS 3R Berkah Real Waste Bank is to become a pilot project in managing non-biodegradable waste with appropriate technology so as to reduce the amount of waste in the TPA Troketon Village, Pedan District. Pandes, Wedi District, Klaten Regency.The implementation methods in this program are Observation of Previous Waste Burning Equipment, Assistance in making the optimization of the Incinerator, Making the Garbage Burner holder at the TPS 3R Berkah Real, Assisting in the operation of the equipment to Partners of the Waste Bank TPS 3R Berkah Real Pandes, Promotion of the use of tools from Partners of the Pandes Blessing TPS Waste Bank to the management of the 3R Blessings Real TPS in Pandes Village, Wedi District, Klaten Regency and Evaluation of activities.